Climate Comfort Changes and Its Response to Meteorological Factors in Liaoning Province - CAO Yongqiang; ZHAO Hui; LI Kexin; YANG Xueting; ZHOU Shuhan (Renmin Zhujiang)
Climate comfort is a bio-meteorological index developed to evaluate the comfort state of the human body under different weather/climate conditions from a meteorological perspective,and it is an important factor affecting human activities and the living environment.In this paper,the comfort index of the human body (CIHB) and the corresponding numbers of comfortable days of different grades in Liaoning Province were counted on the basis of the observation data of 23 meteorological stations in Liaoning Province for many years,and the influences of meteorological factors on human body comfort in various environments were analyzed.The following conclusions can be drawn from the results:① In the past 55 years,the meteorological factors in Liaoning Province showed an overall trend of increasing temperature,decreasing wind speed,and decreasing humidity.② Over those years,the annual province-wide number of comfortable days is 7~8 months,and the whole province is within the comfortable range in June.The average CIHB of the province for the 55 years is 45.2.③ The frequency of comfortable days is highest in summer and lowest in winter.The variation of CIHB days indicates that CIHB is more affected by meteorological factors in summer than in winter.④ The meteorological factor most closely correlated with the comfort index is temperature,with a correlation coefficient as high as 0.894.In contrast,wind speed and relative humidity are negatively correlated with it,although relative humidity is the one most weakly correlated with the index among them.